Bone regeneration: The influence of composite HA/TCP scaffolds and electrical stimulation on TGF/BMP and RANK/RANKL/OPG pathways - Helaehil, Júlia Venturini (2025)
The repair of critical-sized bone defects represents significant clinical challenge. An alternative approach is the use of 3D composite scaffolds to support bone regeneration. Hydroxyapatite (HA) and tri-calcium phosphate (β-TCP), combined with polycaprolactone (PCL), offer promising mechanical resistance and biocompatibility. Bioelectrical stimulation (ES) at physiological levels is proposed to reestablishes tissue bioeletrocity and modulates cell signaling communication, such as the BMP/TGF-β and the RANK/RANK-L/OPG pathways. This study aimed to evaluate the use HA/TCP scaffolds and ES therapy for bone regeneration and their impact on the TGF-β/BMP pathway, alongside their relationship with the RANK/RANKL/OPG pathway in critical bone defects. The scaffolds were implanted at the bone defect in animal model (calvarial bone) and the area was subjected to ES application twice a week at 10 µA intensity of current for 5 min each session. Samples were collected for histomorphometry, immunohistochemistry, and molecular analysis. The TGF-β/BMP pathway study showed the HA/TCP+ES group increased BMP-7 gene expression at 30 and 60 days, and also greater endothelial vascular formation. Moreover, the HA/TCP and HA/TCP+ES groups exhibited a bone remodeling profile, indicated by RANKL/OPG ratio. HA/TCP scaffolds with ES enhanced vascular formation and mineralization initially, while modulation of the BMP/TGF pathway maintained bone homeostasis, controlling resorption via ES with HA/TCP.